Micrometry of Goat Oviducts during Follicular and Luteal Phases of Estrous Cycle - Bhesaniya, Monali B; Kumar, Vishnudeo; Sharma, Anil; Talekar, Shivaji H; Zalavadiya, Sunnykumar H (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Present study was carried out to investigate the micrometrical characteristics of oviduct in adult goats during follicular and luteal phases of the estrous cycle. Study revealed that the mucosa of oviduct of goat was highly folded during both the phases. The number, height, and thickness of the primary mucosal folds were more during follicular phase and the values of these parameters were decreased significantly from infundibulum to isthmus. The lining epithelium of all the segments of goat oviduct was pseudostratified columnar, with ciliated and non-ciliated cell, during both phases of the estrous cycle. The average height of the epithelium was higher during the luteal phase and showed a decreasing pattern from the infundibulum to the isthmus during both the phases. The thickness of propria submucosa was higher in luteal phase and difference was significant only in isthmus segment. Thickness of tunica muscularis of all parts of oviduct was significantly higher in luteal phase than the follicular phase. The thickness of propria submucosa, tunica muscularis and tunica serosa increased significantly from infundibulum to isthmus during both the phases.